Metallosupramolecular Photonic Elastomers with Self-Healing Capability and Angle-Independent Color - Tan, Haiying (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.